Importance of Downstream Processing of Natural Astaxanthin for Pharmaceutical Application - Rodríguez-Sifuentes, Lucio; Marszalek, Jolanta Elzbieta; Hernández-Carbajal, Gerardo; Chuck-Hernández, Cristina (Frontiers in Chemical Engineering, 2021)
Astaxanthin (ASX) is a xanthophyll pigment considered as a nutraceutical with high antioxidant activity. Several clinical trials have shown the multiple health benefits of this molecule; therefore, it has various pharmaceutical industry applications. Commercial astaxanthin can be produced by chemical synthesis or through biosynthesis within different microorganisms. The molecule produced by the microorganisms is highly preferred due to its zero toxicity and superior therapeutic properties. However, the biotechnological production of the xanthophyll is not competitive against the chemical synthesis, since the downstream process may represent 70-80% of the process production cost. These operations denote then an opportunity to optimize the process and make this alternative more competitive. Since ASX is produced intracellularly by the microorganisms, high investment and high operational costs, like centrifugation and bead milling or high-pressure homogenization, are mainly used. In cell recovery, flocculation and flotation may represent low energy demanding techniques, whereas, after cell disruption, an efficient extraction technique is necessary to extract the highest percentage of ASX produced by the cell. Solvent extraction is the traditional method, but large scale ASX production has adopted supercritical CO2 (SC-CO2), an efficient and environmentally friendly technology. On the other hand, assisted technologies are extensively reported since the cell disruption, and ASX extraction can be carried out in a single step. Because a high-purity product is required in pharmaceuticals and nutraceutical applications, the use of chromatography is necessary for the downstream process. Traditionally liquid-solid chromatography techniques are applied; however, the recent emergence of liquid-liquid chromatography like high-speed counter-current chromatography (HSCCC) coupled with liquid-solid chromatography allows high productivity and purity up to 99% of ASX. Additionally, the use of SC-CO2, coupled with two-dimensional chromatography, is very promising. Finally, the purified ASX needs to be formulated to ensure its stability and bioavailability; thus, encapsulation is widely employed. In this review, we focus on the processes of cell recovery, cell disruption, drying, extraction, purification, and formulation of ASX mainly produced in Haematococcus pluvialis, Phaffia rhodozyma, and Paracoccus carotinifaciens. We discuss the current technologies that are being developed to make downstream operations more efficient and competitive in the biotechnological production process of this carotenoid.